Politically Connected Independent Commissioners and Independent Directors on the Cost of Debt - Onong Junus, - (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This study examines the relationship between politically connected independent commissioners and independent directors regarding the cost of debt. The sample is all companies listed on the Indonesia Stock Exchange for the 2010–2017 period, totaling 327 companies with a total data value of 1722 firm-year observations. We used the ordinary least squares regression model (OLS) and the Heckman 2SLS method to solve the endogeneity problem. We found that politically connected independent commissioners and politically connected independent directors negatively correlate with the cost of debt. These results indicate the importance of politically connected independent commissioners and independent directors in managing companies, especially in obtaining loans with low interest rates. In addition, our results are robust due to the use of the Heckman 2SLS test. Therefore, this research can contribute to the development of the literature related to corporate governance and political connections in public companies, so that politically connected independent commissioners and independent directors have an essential role in decision-making in companies.